Thuốc chữa bệnh sốt rét từ cây thanh hao - Hoàng, Văn Phiệt (2011)
Tác giả: Hoàng Văn Phiệt; Phạm Hoàng Ngọc; Phạm Gia Điền; Đào Đình Kim; Hoàng Thanh Hương; Mai Văn Trì; Nguyễn Văn Hùng -- Từ khóa: Cây thanh hao; Sốt rét; Chữa bệnh; Cây thuốc